Componentes dinamizadores del currículo en lenguaje desde la perspectiva docente: Dynamic components of the curriculum in language from the teacher's perspective - Peña Guerrero, Nelsy; Martínez Romero, Emma Lucía (Encuentro Educacional, 2024)
Even when teachers follow guidelines from the Ministry of National Education of Colombia (1998; 2006; 2017; 2018), micro curricula are often disconnected from the realities, interests, and needs of students. This gap between the content taught, the methodology, and meaningful learning limits their training to face contemporary challenges. The purpose of the research was to identify the dynamic components of the language curriculum from the teacher's perspective that respond to current educational demands. It is based on contributions from Ritchhart & Church (2020), Swartz (2018), Robinson (2016), Galbán (2016), Harf (2017), Perkins (2015), among others. The work followed a qualitative approach, with the Educational Action Research method developed in three cycles of reflection; the sample corresponded to 22 teachers of first and second grade of Primary Education. Reflection cycle 1 revealed: the dynamization of the language curriculum requires the generation of strategies according to the context; the dynamization of the meso and micro curriculum implies articulating content with significant and diverse activities; incorporation of technologies and transformation of classroom environments; the curricular structure is perceived as organized-comprehensive, distant from reality, with a lack of the emotional component. Reflection cycles 2 and 3 allowed defining the dynamic components of the curriculum such as the transition to novel strategies, flexibility according to needs and interests, management of emotions, reflective evaluation and school-family articulation.